2014
DOI: 10.1039/c4lc00202d
|View full text |Cite
|
Sign up to set email alerts
|

Focusing of sub-micrometer particles and bacteria enabled by two-dimensional acoustophoresis

Abstract: Handling of sub-micrometer bioparticles e.g. bacteria is becoming increasingly important in the biomedical field and in environmental and food analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
116
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(127 citation statements)
references
References 43 publications
6
116
0
Order By: Relevance
“…Antfolk et al recently demonstrated focusing of bacteria using a combination of streaming and a two-dimensional resonance; their paper is not included in Table I, as comparable concentration data was not included; however, impressive performance with polystyrene beads as small as 0.5 µm was shown. 56 Hammarström et al…”
Section: Introductionmentioning
confidence: 99%
“…Antfolk et al recently demonstrated focusing of bacteria using a combination of streaming and a two-dimensional resonance; their paper is not included in Table I, as comparable concentration data was not included; however, impressive performance with polystyrene beads as small as 0.5 µm was shown. 56 Hammarström et al…”
Section: Introductionmentioning
confidence: 99%
“…1. This system even has the added benefit of having been studied extensively and characterized well both theoretically and experimentally in the steady oscillatory state [2,3,10,11,19,21], thus providing a strong benchmark for the present analysis in the transient regime.…”
Section: Numerical Modelmentioning
confidence: 99%
“…We only consider acoustic perturbation in fluids, and treat the surrounding solid material as ideal rigid walls, a good approximation for water channels in glass-silicon systems. Moreover, extensive theoretical and experimental work [2,3,10,11,19,21] has shown that the adiabatic model describes the observed phenomena qualitatively correctly, while thermoviscous effects may lead to relative quantitative changes up to 30%. Thus by employing an adiabatic model, we can provide an analysis of experimental relevance while at the same time restricting the complexity and vast parameter space of the full problem.…”
Section: Basic Adiabatic Acoustic Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…These are generally considered to be a disturbance as they place a practical lower limit on the particle size that can be manipulated by the primary acoustic radiation force. 1,2 However, acoustic streaming can also play an active role in the functioning of such systems, such as particle trapping, 3-7 two-dimensional particle focusing, 8 and particle separation. 9 Most acoustofluidic particle manipulation devices utilise standing wave fields, and the acoustic streaming field is generally dominated by boundary-driven streaming which arises from the acoustic attenuation within the acoustic boundary layer due to the non-slip condition on the walls of the fluid channel.…”
Section: Introductionmentioning
confidence: 99%